2008
DOI: 10.1111/j.1524-4725.2008.34142.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Botulinum Toxin Type A in the Treatment of Focal Axillary Hyperhidrosis

Abstract: Botulinum toxin Type A is an effective and well-tolerated treatment for axillary hyperhidrosis. Timing of repeat injections as determined subjectively by patients is comparable to studies using colorimetric and gravimetric techniques to quantify the severity of sweating prior to the administration of repeat injections. The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Mostly, such measurements were performed in dermatological settings and concerned the results of botox treatment [3, 4, 1317, 19] or iontophoresis [12]. In those methods of treatment, associated with low level of transient complications or side effects, even less stringent approach to qualification will not cause long-term harm to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly, such measurements were performed in dermatological settings and concerned the results of botox treatment [3, 4, 1317, 19] or iontophoresis [12]. In those methods of treatment, associated with low level of transient complications or side effects, even less stringent approach to qualification will not cause long-term harm to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…This condition causes significant problems both in social and private daily life and affects about 2.5% of the population [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…5,7 In conclusion, these preliminary findings show that female patients with idiopathic axillary hyperhidrosis who have lower gravimetric sweat test results could benefit from 35 U of BonTA as a reasonable starting dose which contributes significantly to improving patients' QOL as well as significantly reducing the cost of treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Although there is no placebo comparison used in this study, other literature has shown that placebo has a much lower response rate of 33%. 1,5,7 Subjectively, 55% of patients had significant improvement in their QOL to the point that their hyperhidrosis had little or no impact on them.…”
Section: Discussionmentioning
confidence: 97%